2007
DOI: 10.1136/bjo.2007.119842
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence, severity and risk factors for pterygium in central Myanmar: the Meiktila Eye Study

Abstract: There is a high prevalence of pterygium in central Myanmar, and the risk of developing this condition increases with outdoor occupation. Pterygium in this population is associated with considerable visual morbidity, including blindness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 18 publications
5
52
0
1
Order By: Relevance
“…9 Dry eye, whether associated with pterygium or not, has not been reported to be independent of other factors related to pterygium occurrence. Tobacco use has been reported to be associated, 11 but also as being protective, 12 and to have no relationship 13 with pterygium presence. There is no report on a relationship between tobacco use and pterygium among blacks.…”
mentioning
confidence: 99%
“…9 Dry eye, whether associated with pterygium or not, has not been reported to be independent of other factors related to pterygium occurrence. Tobacco use has been reported to be associated, 11 but also as being protective, 12 and to have no relationship 13 with pterygium presence. There is no report on a relationship between tobacco use and pterygium among blacks.…”
mentioning
confidence: 99%
“…Exposure to UV light is an established risk factor for development of pterygium and believed to be the single most important risk factor [26,44]. Several other studies have also reported an association between outdoor occupation and pterygium development [19,23,29,45]. Forty-seven (47,75.81%) of the 62 pterygium cases were seen in computer users while fifteen (15,26.56%) were seen in non-computer users.…”
Section: Resultsmentioning
confidence: 99%
“…This is probably due to males forming majority (68.00%) of the study sample. Several studies have reported gender to be an independent predictor of pterygium, with males more likely to develop pterygium than females [15,17,20,24,29,[34][35][36][37]. The Tanjong Pagar survey reported males to be five times more likely to develop pterygium than females [38].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…14,[17][18][19] Pterjium prevalansı Amerika Birleşik Devletleri'nde %2-7, Avustralya'da %1,1, Pekin'de %3, Tahran'da %1,3, Myanmar'da tek gözde %19,6, her iki gözde %8, Endonezya'da tek gözde %10, her iki gözde %4,1 saptanmıştır. [20][21][22][23][24][25] Bizim çalışmamızda bu oran %7,8 idi.…”
Section: Discussionunclassified